The Past and Present, Saparan Bekakak of Ambarketawang: a Study of Cultural Transformation - Fitria, Ajeng; Khoirunnisa, Alfi (Centre for Literary and Cultural Studies, 2024)
Saparan Bekakak is an annual tradition organized by the people of Ambarketawang. The series of traditions begin with the creation of bridal dolls, midodareni, arak-arakan, slaughtering of bridal dolls, and closed with slametan. This long-standing tradition, which the Dutch archives refer to as the remnants of sacrifice, underwent a cultural transformation. This happens due to external and internal factors. Therefore, this study aims to reveal the forms of cultural transformation in Saparan Bekakak and the factors that influence it. To analyze this, Koentjaraningrat's theory of the dynamics of society and culture is used. The theory explains that culture can transform due to internal factors, namely innovation and discovery, encouragement of new discoveries, innovation and evolution; and external factors diffusion, acculturation, assimilation. In the Saparan Bekakak ceremony, changes occur from external factors, namely diffusion and acculturation. Diffusion occurs when Javanese remix DJ music moves from social media into the procession of the arak-arakan. Acculturation also occurs when the ceremony uses Islamic prayers while maintaining the non-Islamic practices, namely the pounding of bride dolls, offerings, and others. In addition, cultural changes can occur due to natural changes due to human activities, namely the physical deformation of Gunung Gamping and its transformation into a cultural reserve, as well as the cessation of mining, making the number of sacrificed bridal dolls decrease.